Role of Proton Pump Inhibitor in the Management of Acid-Related Disorders - Elli Arsita; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2014)
Proton pump inhibitor (PPI) is the strongest inhibitor to gastric acid secretion. PPI is effective in all gastricacid disorders, such as: peptic ulcer, gastroesofageal reflux disease, non steroid anti inflammatory drugs (NSAIDs)gastropathy, and Zollinger-Ellison syndrome. Several studies comparing one PPI to another. Although somedifferences have been reported, there are small differences with unclear clinical importance.PPI has side effects that may be related to diarrhea due to Clostridium difficile, pneumonia, hip fracture, vitamin B12 deficiency, and IgE mediated allergic reaction. Several studies revealed strong association but havelimitation in design and sampel size. PPI therapy should be according to indication, dose, and appropriate period.Keywords: proton pump inhibitor, gastric acid disorder, indication, dose, period ABSTRAKPenghambat pompa proton (PPP) adalah inhibitor paling kuat terhadap sekresi asam lambung. PPPefektif untuk terapi semua gangguan asam lambung termasuk ulkus peptikum, penyakit gastroesofageal reflux,gastropati karena obat anti inflamasi non steroid (OAINS), dan sindrom Zollinger-Ellison. Beberapa penelitianmembandingkan beragam PPP satu dengan yang lainnya. Walaupun dilaporkan ada beberapa perbedaan,namun besaran perbedaannya kecil dan tidak jelas kepentingan klinisnya.PPP kemungkinan berkaitan dengan efek samping diare karena Clostridium difficile, pneumonia, frakturpanggul, defisiensi vitamin B12, dan reaksi alergi yang dimediasi IgE. Beberapa penelitian menunjukkanhubungan yang kuat namun memiliki keterbatasan desain dan besaran sampel. Terapi PPP harus sesuai denganindikasi, dosis, dan jangka waktu yang tepat.Kata kunci: penghambat pompa proton, gangguan asam lambung, indikasi, dosis, jangka waktu